Dental Caries and Associated Factors in 3–5-Year-Old Children in Guizhou Province, China: An Epidemiological Survey (2015–2016) - Guan, Min; Nada, Ola A.; Wu, Juan-juan; Sun, Jiang-ling; Li, Na; Chen, Li-ming; Dai, Tai-ming (Frontiers in Public Health, 2021)
Objective: The current study aimed to explore the factors influencing dental caries among 3–5-year-old children in Guizhou Province and the interrelationship between these factors using structural equation modeling (SEM), while meanwhile providing theoretical references to improve the prevention and control strategy. Materials and Methods: A total of 1291 children aged 3-5 years old in Guizhou province were selected by a multi-stage stratified and whole group random sampling to examine the caries prevalence in whole-mouth deciduous teeth crowns, and parents were surveyed with questionnaires to analyze the caries-related factors. SPSS software was used for statistical analysis. Results: The caries prevalence of children aged 3-5 years old in Guizhou province was 63.1%, and the mean dmft was 3.32; the caries filling rate was 0.5%, and there was no statistically significant difference between urban and rural areas and amongst genders in each age group; results of logistic regression analysis showed that the caries risk increased with the following factors; age, brushing frequency less than 2 times per day when parents did not take their children to the dentist, and with parents' poor evaluation of their children's oral condition. The higher the parent's education, the lower the risk of children suffering from deciduous caries. Conclusion: The prevalence of dental caries in deciduous teeth of children aged 3-5 years in Guizhou province is serious, with more than 99% of the caries cases being untreated, and with an overall poor situation in reference to oral hygiene habits, parents' oral health care attitude, and behavior transformation. Therefore, caries prevention and treatment measures of caries in preschool children need strengthening through the improvement of public awareness and the enhancement of the parents' governance of their children's oral health habits enhancement.